Glossary on the World Trade Organisation and public health: part 2. Issue 9 (11th August 2006) - Labonte, Ronald; Sanger, Matthew
Abstract : Part 1 of this glossary introduced different health and trade arguments, overviewed the history of the World Trade Organisation (WTO), defined key "trade talk" terms, and reviewed three WTO treaties concerned with trade in goods (GATT 1994, the Agreement on Agriculture, and the Agreement on Sanitary and Phytosanitary Measures). Part 2 reviews five more agreements and the growing number of bilateral and regional trade agreements, and concludes with a commentary on different strategies proposed to ensure that health is not compromised by trade liberalisation treaties.